Design of Automatic Transfer Switch ACOS with Human Machine Interface Monitoring System in Shipboard Application - Sardono Sarwito; Indra Ranu Kusuma; Boy Hendra Waramory (International Journal of Marine Engineering Innovation and Research, 2016)
This paper concern about design ACOS with PLC system. The supply of electricity will move from the main generator to the battery when the main generator lost one phase, and the power supply will switch to the emergency generator when the voltage in accordance with the emergency generator working voltage AC electrical equipment on board is 380VAC. Electricity supply shall not move directly from the emergency generator to the main generator but to the battery first to prevent damage to the AC electrical equipment on board.  Transport time for the system for 30 seconds ACOS equipment in accordance with the ICC and SOLAS regulations which require the transfer of under 45 seconds. ACOS equipment can be used in real conditions on the ship because it has phase failure, under voltage and over voltage protection and a relay as an indication for the transfer of command power supply automatically.